Evaluation of error in TRMM 3B42V7 precipitation estimates over the Himalayan region. Issue 24 (22nd December 2015) - Bharti, Vidhi; Singh, Charu
Abstract: Accurate precipitation measurement is crucial for weather forecasting and hydrological modeling. Tropical Rainfall Measuring Mission (TRMM) 3B42V7 satellite precipitation product offers an opportunity to monitor precipitation at high spatiotemporal resolution. However, it has several inherent errors related to observation, instrument, and rainfall retrieval algorithms. It is, therefore, essential to validate it with ground‐based measurements. We divide the region into different elevation ranges and compare 3B42V7 with India Meteorological Department gauge‐based measurements, so as to observe the behavior of satellite at different altitudes. This paper evaluates error characteristics of 3B42V7 using continuous and categorical validation schemes. The analysis reveals 3100 m altitude as the breakpoint for the satellite overestimating and underestimating rainfall amount for elevation ranges below and above it, respectively. It gives a poor positive correlation of ~0.23 between individual rainfall events, though the correlation improves (~0.67) for areal‐averaged precipitation values. 3B42V7 also underestimates the frequency of actual rainfall events and is not very good at identifying correct rain and no‐rain events with the overall accuracy of ~66%. Conclusively, the satellite exhibits comparatively better performance for 1000–2000 m elevations but exacerbates over higher‐altitude regions. Further, we assess its capability for very heavy rainfall events using three percentile thresholds. The low‐magnitude bias for 98th and 99th percentiles and high‐magnitude bias for 99.99th percentile imply that 3B42V7 may not be suitable for the study of very heavy rainfall events. On the basis of these findings, it is recommended to improve satellite precipitation retrieval algorithms by incorporating topographical and local climatic factors into consideration. Key Points: TRMM 3B42V7 is validated with rain gauge data over the Himalayan region Satellite data give poor overall accuracy in correctly identifying rainfall events 3B42V7 may not be suitable for the study of very heavy rainfall events in the region